2015
DOI: 10.1007/s10529-015-2000-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Saccharomyces cerevisiae for linalool production

Abstract: Although overexpression of tHMG1 and downregulation of ERG9 enhanced linalool titers threefold in the engineered yeast strain, alleviating linalool toxicity is necessary for further improvement of linalool biosynthesis in yeast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 26 publications
2
41
0
1
Order By: Relevance
“…However, this strain showed a dramatic growth deficiency and required a 14-day cultivation (20 g L -1 glucose) to obtain this titre. In other engineered microbial strains, linalool production titres remain in the μg L -1 scale (Amiri et al, 2016;Rico et al, 2010). The highest titres for other monoterpenes in batch cultivation in engineered microorganisms are currently 41 mg L -1 for sabinene in E.coli (Zhang et al, 2014), 32 mg L -1 for pinene in E.coli (Sarria et al, 2014), 66 mg L -1 for geraniol in S. cerevisiae (Zhao et al, 2016), 69 mg L -1 for geraniol in E.coli (Liu et al, 2016), and 24 mg L -1 for limonene in Yarrowia lipolytica (Cao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this strain showed a dramatic growth deficiency and required a 14-day cultivation (20 g L -1 glucose) to obtain this titre. In other engineered microbial strains, linalool production titres remain in the μg L -1 scale (Amiri et al, 2016;Rico et al, 2010). The highest titres for other monoterpenes in batch cultivation in engineered microorganisms are currently 41 mg L -1 for sabinene in E.coli (Zhang et al, 2014), 32 mg L -1 for pinene in E.coli (Sarria et al, 2014), 66 mg L -1 for geraniol in S. cerevisiae (Zhao et al, 2016), 69 mg L -1 for geraniol in E.coli (Liu et al, 2016), and 24 mg L -1 for limonene in Yarrowia lipolytica (Cao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, enzymes from the mevalonate (MVA) pathway were over-expressed to increase precursor flux for terpene synthesis (Figure 1) (Peng et al, 2017a;Peng et al, 2017b;Vickers et al, 2017). A dedicated GPP synthase has been used to increase the GPP pool for monoterpene production (Alonso-Gutierrez et al, 2013;Amiri et al, 2016;Cao et al, Liu et al, 2016;Rico et al, 2010;Sarria et al, 2014;Willrodt et al, 2014;Zhang et al, 2014). However, yields were low compared to production of sesquiterpenes in a similar system, suggesting that the native Erg20p competes effectively with the monoterpene synthase for GPP.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to gene knock-out strategies, re-directing metabolic fluxes by tuning the expression of essential genes encoding competing pathway steps is another strategy often used to improve biobased production. This has traditionally been accomplished by integrating inducible or repressible promoters to control the expression of flux controlling genes amenable to transcriptional regulation [7, 29, 40]. More recently, CRISPR/dCas9 has been adopted for redirecting metabolic fluxes through transcriptional regulation of single and multiple genes [21, 22, 24, 41].…”
Section: Discussionmentioning
confidence: 99%
“…4). Several terpene synthases from fungal, plant, and bacterial origin have been reported to produce linalool (Crowell et al, 2002;Dudareva et al, 1996;Jia et al, 1999;Landmann et al, 2007;Pichersky et al, 1995) but only a few studies have shown microbial production of this molecule at low titers (Amiri et al, 2016;Thanasomboon et al, 2012). We cloned the truncated 3R-linalool synthase, in which the plastidial transit peptide was deleted, from M. citrate (Crowell et al, 2002) into the 1P, 2P, and 2P Ã systems, and they were transformed and tested for production in both wild type and the ispA mutant DH1 host strains.…”
Section: Production Of Other Jet Fuel Precursor Monoterpenesmentioning
confidence: 99%